PREVENTION OF PSYCHOACTIVE SUBSTANCE USE AMONG YOUNG PEOPLE AS A SOCIALLY PEDAGOGICAL PROBLEM - Vilks, Andrejs (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2016)
In the century of modern technologies the human behaviour models are changing, new types of addiction are developing, including addiction to processes (cyber, games addiction), as well as addiction to new substances. Among young people there is observed an increased spreading of new psychotropic substances, manufacturing of which is very simple, but their realization determines possibilities for a markedly great profit. In the cultural environment of young people the new traditions are formed, specific elements of subculture, positive attitude towards being able to use and apply something new. A new value system is developing with a sense of unlimited freedom and extensive rights. Along with the chances to buy and use new psychoactive substances, the changes occur also in the young people’s psyche, affecting their emotional and physical condition. A new, socially-pedagogical approach is needed in restriction of the use of these new psychoactive substance.